Early life air pollution exposures and thyroid function in children: A prospective cohort study - Heo, You Joung; Lee, Yun Jeong; Kim, Soon Tae; Lee, Dong Wook; Kim, Johanna Inhyang; Kim, Bung Nyun; Hong, Yun Chul; Shin, Choong Ho; Lee, Young Ah; Lim, Youn Hee (Environmental Pollution, 2024)
Studies on early life ambient air pollution exposures and childhood thyroid function are scarce. This study aimed to evaluate the relationships between early life fine particulate matter (≤2.5 μm; PM2.5) and nitrogen dioxide (NO2) exposures and thyroid function in children. We measured the levels of thyrotropin, triiodothyronine, and free thyroxine in children (n = 684) residing in a rural Korean area at age 2, 4, 6, or 8 years from 2012 to 2020 in the Environment and Development of Children cohort. The relationship between residential average exposure levels of PM2.5 and NO2 during pregnancy and 1-year average levels before visit and thyroid function during childhood were analyzed. Inverse association between increases of 10 μg/m3 in PM2.5 during the first trimester and thyrotropin levels at aged 4 (β, −0.12; 95% CI: −0.22, −0.02) and 6 years (β, −0.16; 95% CI: −0.26, −0.06) were observed. No association was found between PM2.5 exposure during the second and third trimester and childhood TSH levels. Childhood PM2.5 exposure was positively associated with thyrotropin rise at aged 4 (β, 0.2; 95% CI: 0.06, 0.35) and 6 years (β, 0.16; 95% CI: 0.02, 0.29) and inversely related with free thyroxine levels at aged 8 years (β, −0.04; 95% CI: −0.07, −0.01). No relationship between NO2 exposure and thyroid function was found. In conclusion, association between PM2.5 exposure and childhood thyrotropin levels varied depending on exposure timing. Early gestational exposure showed an inverse relationship, whereas childhood exposure were positively associated with childhood thyrotropin levels. The long-term effects of early life air pollution exposure and underlying mechanisms should be investigated in future studies.
Keywords: Air pollutants; Air pollution exposures; Child; Earliest life; Function tests; Nitrogen dioxides; Particulate Matter; PM 2.5; Thyroid function; Thyroid function test; Air Pollutants; Air Pollution; Child; Child, Preschool; Cohort Studies; Environmental Exposure; Female; Humans; Male; Nitrogen Dioxide; Particulate Matter; Pregnancy; Prospective Studies; Republic of Korea; Thyroid Gland; Thyrotropin; Thyroxine; Triiodothyronine; Air pollutants; Children; Nitrogen dioxide; Particulate matter; Thyroid function test